Antitubercular and cytotoxic tigliane-type diterpenoids from Croton tiglium. Issue 20 (15th October 2016) - Zhao, Bi-Qing; Peng, Shuai; He, Wei-Jun; Liu, Yong-Hong; Wang, Jun-Feng; Zhou, Xiao-Jiang
Graphical abstract: Abstract: Five new tigliane diterpene esters (1 –5 ), highly oxygenated tetracyclic diterpenoid carbon skeleton, together with three known analogues (6 –8 ) were isolated from the leaves of Croton tiglium . Extensive NMR and mass spectroscopic analysis were used to elucidate their structures. Most of the isolated compounds were tested for their cytotoxic and antitubercular activities. Among them, the cytotoxic activities of these tigliane-type diterpenes strongly depend on the species of the tumor cells. Especially, these bioactivity compounds showed strong cytotoxic activities against the K562 cell line, and their inhibition effects were close to the positive control Taxol. Furthermore, compounds1, 2, 6, and7 showed potent antitubercular activities with MIC values of 19.5, 20.9, 20.5, and 13.4 μM, respectively.